SUS-30 years: right and access in a day in the life of Primary Health Care - Selma Maria da Fonseca Viegas; Leila Cristine do Nascimento; Cássia Menezes; Thiago Rocha Santos; Gabriel Rios Roquini; Adriana Dutra Tholl; Rosane Gonçalves Nitschke
ABSTRACT Objectives: to understand access in a day in the life Primary Health Care as a fundamental right to health, from users' perspective. Methods: a holistic-qualitative multiple case study based on Comprehensive Sociology of Everyday Life. 77 Unified Health System (SUS) users participated in the study. Results: according to users' voice, the right to health is still a matter of struggle, in more than 30 years of SUS. SUS is considered as the place where they have to appeal. The experiences are diverse, from the ease to the difficulty of access, neglecting users' needs, but despite the inequality in relation to the offer of services, the solution always arrives. Final Considerations: to overcome this historical obstacle of comprehensive access to health, as a fundamental human right, it is necessary to overcome political and administrative decisions that hinder the construction of legitimate SUS, in a truly democratic participation of all social actors.